ENLIGHTENED CONVERSATIONS: THE CAREER AND CONTRIBUTIONS OF ANTHONY J. LA VOPA. (2nd October 2015) - MARCHAND, SUZANNE
Abstract : If you have never had a conversation with Tony La Vopa—and I mean a serious, four-hour conversation, in which topics range from Rousseau to the Final Four to marzipan to Kant—you have missed out on one of academia's great pleasures. Tony is one of intellectual history's most beloved conversationalists: because he knows many things, because he loves to tell stories, because he listens, because he argues. He also, incidentally, has mastered the pithy, but somehow personal, email: he once wrote me, simply "You're not resting, " and another time: "I'm alarmed about your porcelain addiction." Those readers who know Tony only from his work on this journal or his published works will know the clarity, deep intelligence, and admirable density of his research and his editing, but may not know much about the conversations that he has sustained and that have sustained him across his career, and haven't caught the impish glint in his eye when he launches into a story about his own current fetishes (photography, gooseberry Küchen ), or lightly, invitingly, teases you about your own (according to Tony, mine include "loony men in gray suits"). And so, having had the pleasure of being a friend, coconspirator, and conversation partner of Tony's for several decades now, I have gladly accepted the honor of further acquainting Modern Intellectual History 's readership with the career and contributions (so far!) of Anthony J. La Vopa, whose work has done so much to make intellectual history the thriving field it is today.